1995
DOI: 10.1063/1.469666
|View full text |Cite
|
Sign up to set email alerts
|

A resonance enhanced multiphoton ionization study of the CS2 molecule: The 4p Rydberg states

Abstract: The resonance enhanced multiphoton ionization (REMPI) spectrum of jet-cooled CS2 has been recorded in the one-photon wavelength range 460–500 nm, corresponding to the three photon excitation energy range 60 000–65 000 cm−1. A previous assignment of one photon forbidden transitions in this region to 3d Rydberg states is shown to be incorrect and reassigned to the 4pπ 1,3Δu states. In fact all the observed states in this region can be assigned to 4p Rydberg states; the 4pσ 1,3Πu states at 62 768 and 62 083 cm−1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 27 publications
6
43
0
Order By: Relevance
“…5͑a͔͒ was obtained following excitation at 483.1 nm ͑3ṽϭ62 100 cm Ϫ1 ͒; the kinetic energy of the major peak ͑0.188 eV͒ is consistent with ionization to the v ϩ ϭ0 ͑shorthand notation for v 1 ϩ ϭv 2 ϩ ϭv 3 ϩ ϭ0͒ level of the lower, ͓3/2͔, spin-orbit component of the ion thus implying, by Franck-Condon arguments, that the resonance enhancement also involves an electronic origin, almost certainly that of a Rydberg state built on the ͓3/2͔ ion core. Such a conclusion is fully consistent with that reached in a number of previous analyses; 8,10,13,39 namely, that this feature should be assigned as the origin of the resonance. The associated REMPI-PE spectra shown in Figs.…”
Section: Figsupporting
confidence: 79%
See 4 more Smart Citations
“…5͑a͔͒ was obtained following excitation at 483.1 nm ͑3ṽϭ62 100 cm Ϫ1 ͒; the kinetic energy of the major peak ͑0.188 eV͒ is consistent with ionization to the v ϩ ϭ0 ͑shorthand notation for v 1 ϩ ϭv 2 ϩ ϭv 3 ϩ ϭ0͒ level of the lower, ͓3/2͔, spin-orbit component of the ion thus implying, by Franck-Condon arguments, that the resonance enhancement also involves an electronic origin, almost certainly that of a Rydberg state built on the ͓3/2͔ ion core. Such a conclusion is fully consistent with that reached in a number of previous analyses; 8,10,13,39 namely, that this feature should be assigned as the origin of the resonance. The associated REMPI-PE spectra shown in Figs.…”
Section: Figsupporting
confidence: 79%
“…1 and 3. In fact, as Baker et al 39 have demonstrated ͑and we confirm but do not show in Fig. 4͒, ion fragmentation can also give rise to local intensity variations in the mass selected REMPI spectrum of CS 2 : The 3ϩ1 REMPI spectrum shown in Fig.…”
Section: Methodsmentioning
confidence: 50%
See 3 more Smart Citations